Performance of sweet potato varieties in hilly area - Shaheenuzzamn, M; Saha, RR; Biswas, A; Islam, MS (Bangladesh Agronomy Journal, 2015)
The experiment was conducted at the research field of Hill Tract Agricultural Research Station. Ramgarh, Khagrachari during Rabi season of 2012-2013 and 2013-14. Five different sweet potato varieties (BARI Sweetpotato-6, BARI Sweetpotato-7, BARI Sweetpotato-8, BARI Swwetpotato-9 and local cultivar were included as treatment variables in the experiment. BARI Sweetpotato-7 had significantly more number of vines (8.30) as compared to local cultivar and other new varieties such as BARI Sweetpotato-6, BARI Sweetpotato-8 and BARI Sweetpotato-9. Maximum number of tuber plant-1 (5.4 and 5.3), tuber length (15.30 and 15.80 cm), tuber diameter (5.10 and 5.20 cm), individual tuber weight (368.35 and 377.69 g) and tuber yield (19.89 and 20.13 t ha-1) was recorded from BARI Sweetpotato-9 during 2012-13 and 2013-14, respectively whereas local cultivar gave minimum values. The variety BARI Sweetpotato-9 out yielded local cultivar by 108.93 and 103.13 % during two consecutive years but highest net income (3,10,818 and 3, 15,617 Tk. ha-1) from BARI Sweetpotato-7 Bangladesh Agron. J. 2014, 17(2): 83-87